Constraints on Light Neutrino Parameters Derived from the Study of Neutrinoless Double Beta Decay - Sabin Stoica; Andrei Neacsu (Advances in High Energy Physics)
The study of the neutrinoless double beta (0νββ) decay mode can provide us with important information on the neutrino properties, particularly on the electron neutrino absolute mass. In this work we revise the present constraints on the neutrino mass parameters derived from the 0νββ decay analysis of the experimentally interesting nuclei. We use the latest results for the phase space factors (PSFs) and nuclear matrix elements (NMEs), as well as for the experimental lifetime limits. For the PSFs we use values computed with an improved method reported very recently. For the NMEs we use values chosen from the literature on a case-by-case basis, taking advantage of the consensus reached by the community on several nuclear ingredients used in their calculation. Thus, we try to restrict the range of spread of the NME values calculated with different methods and, hence, to reduce the uncertainty in deriving limits for the Majorana neutrino mass parameter. Our results may be useful to have an updated image on the present neutrino mass sensitivities associated with 0νββ measurements for different isotopes and to better estimate the range of values of the neutrino masses that can be explored in the future double beta decay (DBD) experiments.